RAPTOR: Randomised Controlled Trial of PENTOCLO (pentoxifylline-tocopherol-clodronate) in Mandibular Osteoradionecrosis—study protocol for an open-label phase II randomised controlled superiority trial - Richard Shaw; Ruth Knight; Ayten Basoglu; Mandeep Bajwa; Julie Perry; Anastasios Kanatas; Stefano Fedele; Vincent Killen; Rebecca Tangney; Chris Butterworth; James McCaul; Jagtar Dhanda; et al. (Trials)
Abstract Background Mandibular osteoradionecrosis (ORN) is a severe late radiation toxicity affecting 5–10% of patients who receive radiotherapy as part of treatment for head and neck malignancy. ORN can cause permanent disfigurement, dysfunction, pain and infection. There remains little robust evidence supporting the efficacy of medical or surgical management currently offered in clinical practice. Retrospective case series and meta-analyses of observational studies suggest that a repurposed triple drug combination pentoxifylline-tocopherol-clodronate (‘PENTOCLO’) may be effective in preventing deterioration, promoting healing and ultimately reducing the need for major reconstructive surgery. Methods The RAPTOR trial is a phase II, open-label, multicentre, randomised controlled trial with a superiority design. Eligible subjects with mandibular ORN are randomised 1:1 to receive standard of care (Arm A) or PENTOCLO plus standard of care (Arm B) for 12 months. The primary outcome measure is time from randomisation to healing of ORN (without the need for surgery), as measured by clinical examination (confirming completely healed oral mucosa), intra-oral clinical photographs and imaging. RAPTOR has an embedded translational sample collection and a methodological component exploring the use of electronic patient-reported outcome measures (ePROM). Discussion The RAPTOR trial is the first randomised controlled clinical trial of PENTOCLO in this clinical setting. The results of this phase II trial will provide robust preliminary evidence on its efficacy and inform the feasibility and appropriateness of a subsequent definitive trial. Trial registration RAPTOR is registered with the ISRCTN registry effective date 11th November 2022: Clinical trial of the non-surgical management of radiotherapy damage to the lower jaw ISRCTN34217298, and also registered with the European Clinical Trials Database (Eudra-CT 2022–000728-39).